Restaurant reservation system using electronic customer relationship management / Nik Marsyahariani Nik Daud and Muhammad Amin Abdul Aziz - Nik Daud, Nik Marsyahariani; Abdul Aziz, Muhammad Amin (2019)
In this era of technology, online reservation system has been applied in many organizations to reserve many type of appointments. Makette Restaurant, a restaurant with steamboat and grill concept is currently using manual process to handle their reservation process. Customer is required to come to the restaurant in order to reserve table in the restaurant which is inefficient. To overcome the problem, a system name Makette Steamboat & Grill Reservation System (E-MASTERS) is developed using System Development Life Cycle (SDLC) methodology with Adapted Waterfall Model. Electronic Customer Relationship Management (eCRM) is implemented in E-MASTERS to improve customer satisfaction while using the system. The prototype of E-MASTERS is tested and evaluated in term of functionality and usability by three (3) expert evaluators from different background and thirty (30) respondents. Respondents deemed the system is easy to use based on the result. Future work involves more implementation of eCRM to improve the system from customer satisfaction aspect.